Pitfalls of Contracting for Policy Advice: Preparing Performance Budgeting Reform in Estonia. Issue 4 (20th November 2012) - Raudla, Ringa
Abstract : The goal of this article is to analyze the challenges involved in contracting for policy advice with the example of performance budgeting reform in Estonia in 2009–2011. The Estonian Ministry of Finance has sought to prepare a major change in the budgeting system by outsourcing the analytical preparation of different aspects of the reform to various private sector organizations. The case study seeks to identify the challenges and pitfalls involved in contracting for policy and management advice in the area of a major public sector reform. The Estonian experience shows that such a reform strategy can run into serious problems, including fragmented and inconsistent reform plan, limited learning, and high transaction costs. The contractualization of reform preparation has constrained deliberations on the planned changes to the strategic planning and budgeting system among the stakeholders and undermined the democratic legitimacy of the reform.